R" is for Ricochet - Grafton, Sue (New York Putnam Publishers, 2004)
An assignment to "babysit" Reba Lafferty, a wealthy and spoiled young woman just out of prison on probation from the California Institution for Women for embezzlement, turns unexpectedly dangerous for Kinsey Milhone.
Keywords: Women private investigators -- California -- Ex-convicts